William Paley, William Buckland and the Oxford University Museum - Peacocke, Emma (Romanticism on the Net, 2018)
The Oxford University Museum of Natural History appears to be quintessentially Victorian, with its iron-and-glass architecture. It even bears the seal of approval of the great doyen of Victorian taste, John Ruskin (1819-1900). However, this museum also embodies William Paley’s (1743-1805) Romantic-era Christian philosophy of divine design. Paley was the great synthesizer of the tradition of Natural Theology, which held that God’s benevolence and ingenuity could be “read” from nature just as they could from the Bible. I argue that Paley’s influence persisted long after the Romantic era and pervaded the Oxford University Museum (founded 1860) and its program of architectural decoration. To enter the museum, we walk under the arm of the carved angel who holds the book of nature. The teaching and popular writings of the clergyman and geologist William Buckland (1784-1856) also form a bridge between Paley and the Oxford University Museum. Buckland’s pupils included Ruskin and Henry Acland, two of the great advocates of the Oxford University Museum. Buckland’s popular Bridgewater Treatise (1836) exemplifies Natural Theology, and features an imaginary walk through the mineral deposits of Britain. Paralleling this imaginary walk, the Oxford University Museum had columns made from different kinds of British stone. In these ways—and in others that this essay explores—this groundbreaking Victorian building quite literally embodies a much older intellectual heritage.